Being in a position to know: attuned responsiveness as the hallmark of experiential knowledge and expertise in mental healthcare - Dings, Roy; Strijbos, Derek W. (Frontiers in Psychiatry, 2025)
Inclusion of people with lived experience into various mental healthcare settings is rapidly increasing. In this article we explicate and address two challenges that hinder this development. First, a descriptive challenge: what is the unique and complementary epistemic contribution of people with lived experience in mental healthcare, precisely? Second, a normative challenge: how to evaluate these contributions of people with lived experience to mental healthcare? To address these challenges, we propose a novel conceptual ‘lens’ through which to understand the epistemic contributions of people with lived experience. Our approach diverges from the orthodox view by not construing these contributions in terms of (experiential) knowledge, but in terms of perceptual and agential skills which put people with lived experience in a unique ‘position to know’. More specifically, we reckon that such contributions are best understood in terms of what we call ‘responsiveness’ and ‘attunement’. The main goal of this paper is to show how the ‘Attuned Responsiveness’-Framework allows us to satisfactorily address the descriptive and normative challenge, thereby providing the practice of expertise-by-experience in mental healthcare with a more solid conceptual basis.